Speech Etiquette In English And Uzbek: A Pragmalinguistic Analysis - Usmonova, Dono Sotvoldievna; Ergasheva, Shakhnoza Erkinovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The present article is a comparative analysis of the pragmalinguistic features of the speech etiquette of the English and Uzbek languages. Speech etiquette is a significant aspect of communicative competence that mirrors the values of the culture, the social order, and the personal ties of the respective linguistic community.